Preparation method and application of modified rutile type nano titanium dioxide

Through the preparation and surface modification of modified rutile nanotitanium dioxide and combined with polymerization reaction, the dispersion and compatibility problems of rutile nanotitanium dioxide in polystyrene are solved, and the tensile properties and high temperature resistance of the material are significantly improved. , achieving better enhancement effect and anti-UV aging performance.

CN119286060AActive Publication Date: 2025-01-10GUANGDONG HUI YUN TITANIUM IND CORP LTD

Patent Information

Application Number
CN202411423049.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-01-10
Estimated Expiration
2044-10-12

AI Technical Summary

Technical Problem

Rutile nanotitanium dioxide has poor dispersion and poor compatibility in polystyrene materials, resulting in poor reinforcement effect, especially insufficient high temperature resistance and mechanical strength.

Method used

Rutile nanotitanium dioxide was prepared by hydrothermal method, and the surface modification of toluene-2,4-diisocyanate was modified, combined with bis(4-aminophenoxy)dimethylsilane and glycidyl methacrylate to form a modification rutile nanotitanium dioxide is melt blended to improve the tensile properties and high temperature resistance of polystyrene.

Benefits of technology

It significantly improves the dispersion and compatibility of modified rutile nanotitanium dioxide in polystyrene, enhances the tensile strength, elongation of break and resistance to UV aging, and improves the high temperature resistance and heat resistance of the material. Decomposition temperature.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005081390720000021
    Figure BDA0005081390720000021
  • Figure BDA0005081390720000061
    Figure BDA0005081390720000061
  • Figure BDA0005081390720000081
    Figure BDA0005081390720000081
Patent Text Reader

Abstract

The invention belongs to the technical field of titanium dioxide composite materials, and discloses a preparation method and application of modified rutile type nano titanium dioxide. According to the preparation method, water and n-hexyl alcohol are taken as a microemulsion system, titanium tetrachloride is taken as a titanium source, lauryl sodium sulfate is taken as a surfactant, and rutile type nano titanium dioxide with good dispersity and small particle size is obtained through hydrothermal reaction; then carrying out surface modification by using toluene-2, 4-diisocyanate, so as to obtain modified rutile type nano titanium dioxide; and carrying out melt blending with a copolymer of styrene and an acrylate dimethylsilane monomer by taking the modified polystyrene as a filler to obtain the polystyrene material. Isocyanate groups contained on the surface of the modified rutile type nano titanium dioxide can react with hydroxyl groups of the polystyrene copolymer, so that the mechanical property, the high temperature resistance and the ultraviolet aging resistance of the material are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of titanium dioxide composite materials, and in particular relates to a preparation method and application of modified rutile nano titanium dioxide. Background Art

[0002] Rutile nano-titanium dioxide has good ultraviolet absorption performance, large specific surface area, high mechanical strength, and is widely used in polymer materials such as polystyrene, polyethylene, and polyurethane. It can be used as a toughening agent and anti-ultraviolet absorber to improve the mechanical properties and anti-ultraviolet aging properties of materials. However, rutile nano-titanium dioxide is prone to agglomeration, and its compatibility with the polymer material matrix is ​​poor, resulting in poor reinforcement effect. Improving the compatibility and interface properties between materials and nano-titanium dioxide is a research hotspot.

[0003] Polystyrene is a common polymer material with a simple preparation method and low cost. It can be made into foam, plastic, film, fiber and other products, and is widely used in packaging, containers, insulation materials, optical components, etc. Patent publication number CN118256042A discloses that rutile titanium dioxide loaded with antimony tin oxide is used as a coating to give polystyrene foaming material antistatic properties and flame retardant properties. However, the patent does not improve the high temperature resistance and mechanical strength of polystyrene materials. Summary of the invention

[0004] The technical problem solved by the invention is to provide a preparation method and application of modified rutile nano titanium dioxide, solving the problems of poor dispersibility of rutile nano titanium dioxide and poor compatibility with polystyrene materials.

[0005] The technical solution of the present invention is: a method for preparing modified rutile nano-titanium dioxide, comprising the following steps:

[0006] Step (1), adding water and titanium tetrachloride to a reaction vessel under an ice bath, stirring, adding n-hexanol and sodium dodecyl sulfate, stirring and mixing, pouring the solution into a reaction kettle, filtering after the reaction, washing with water and ethanol in turn, and drying to obtain rutile nano-titanium dioxide.

[0007] Step (2), adding toluene and rutile nano-titanium dioxide into a reaction container, dispersing by ultrasonication, then adding toluene-2,4-diisocyanate, heating to 100-110° C., reacting for 2-3 hours, filtering, washing with toluene, and drying to obtain modified rutile nano-titanium dioxide.

[0008] Preferably, in step (1), the ratio of water, titanium tetrachloride, n-hexanol and sodium dodecyl sulfate is 1L:(120-200)g:(6-7)L:(80-130)g.

[0009] Preferably, the reaction temperature in step (1) is 80-100° C. and the reaction time is 12-18 h.

[0010] Preferably, in step (2), the ratio of rutile nano-titanium dioxide to toluene-2,4-diisocyanate is 1 g:(0.4-1) g.

[0011] Preferably, the modified rutile nano-titanium dioxide is used in high temperature resistant and anti-aging polystyrene.

[0012] Preferably, the method for preparing the high temperature resistant and aging resistant polystyrene comprises the following steps:

[0013] Step A: Add tetrahydrofuran, bis(4-aminophenoxy)dimethylsilane and glycidyl methacrylate in a ratio of 1 g:(1.03-1.1) g to a reaction vessel, heat to 40-50°C, stir to react for 3-5 hours, distill under reduced pressure, wash with petroleum ether and acetone in turn, and dry to obtain acrylate dimethylsilane monomer. The preparation reaction formula is:

[0014]

[0015] Step B: add toluene, styrene and acrylate dimethylsilane monomer into a reaction container, introduce nitrogen, add azobisisobutyronitrile, heat to 70-85° C., react for 7-10 hours, distill under reduced pressure, wash with ethanol, and dry to obtain a polystyrene copolymer.

[0016] Step C, adding polystyrene copolymer, modified rutile nano-titanium dioxide and antioxidant into a twin-screw extruder, with the temperature of sections 1-5 being 190-220° C., melt blending, extrusion and granulation to obtain high temperature resistant and anti-aging polystyrene.

[0017] Preferably, in step B, the mass ratio of styrene to acrylate dimethylsilane monomer is 1 g:(0.1-0.3) g.

[0018] Preferably, in step C, the mass ratio of the polystyrene copolymer to the modified rutile nano-titanium dioxide is 100 g:(0.5-4) g.

[0019] Technical effect: The present invention uses water and n-hexanol as a microemulsion system, titanium tetrachloride as a titanium source, and sodium dodecyl sulfate as a surfactant, and obtains rutile nano-titanium dioxide with good dispersibility and small particle size through a hydrothermal reaction; then, the surface is modified using toluene-2,4-diisocyanate to obtain modified rutile nano-titanium dioxide containing isocyanate groups on the surface.

[0020] The invention carries out a ring-opening reaction on bis(4-aminophenoxy)dimethylsilane and glycidyl methacrylate to obtain an acrylate dimethylsilane monomer, which is then copolymerized with a styrene monomer to obtain a polystyrene copolymer, and finally melt-blended with modified rutile nano-titanium dioxide as a filler to obtain high-temperature resistant and anti-aging polystyrene.

[0021] After the rutile nano-titanium dioxide of the present invention is modified by toluene diisocyanate, its dispersibility is better, and its compatibility with the polystyrene copolymer matrix is ​​excellent, which is conducive to improving the tensile properties of polystyrene; at the same time, the isocyanate group contained on the surface of the modified rutile nano-titanium dioxide can react with the hydroxyl group of the polystyrene copolymer during high-temperature melt blending in a screw extruder, thereby grafting the nano-titanium dioxide into the polystyrene copolymer molecular chain, enhancing the bonding strength between the two, making the nano-titanium dioxide play a better reinforcing role, and further improving the tensile strength and elongation at break of polystyrene. In addition, the rutile nano-titanium dioxide has a strong ultraviolet absorption capacity, is evenly dispersed in the polystyrene matrix, and significantly improves its anti-ultraviolet aging performance.

[0022] The polystyrene copolymer molecular chain of the invention contains a diphenylsiloxane structure, has strong heat resistance, good anti-thermal decomposition performance, and is conducive to improving the heat resistance of the material. In addition, the isocyanate group of the modified rutile nano-titanium dioxide reacts with the hydroxyl group of the polystyrene copolymer, so that the nano-titanium dioxide and the polystyrene form a chemical cross-linking effect, which increases the cross-linking degree of the polystyrene molecular chain, restricts the movement of the molecular chain, thereby increasing the thermal decomposition temperature of the polystyrene material, showing a higher initial thermal decomposition temperature and a maximum thermal decomposition rate temperature, and significantly improving the high temperature resistance of the material. DETAILED DESCRIPTION

[0023] In order to understand the technical features and contents of the present invention in detail, the preferred embodiments of the present invention will be described in more detail below. Although the preferred embodiments of the present invention are described in the embodiments, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments described here.

[0024] Example 1

[0025] Step (1), add 100 mL of water and 20 g of titanium tetrachloride to a reaction vessel under an ice bath, stir, add 700 mL of n-hexanol and 13 g of sodium dodecyl sulfate, stir and mix, pour the solution into a reaction kettle, heat to 90° C., react for 18 hours, filter, wash with water and ethanol in turn, and dry to obtain rutile nano-titanium dioxide.

[0026] Step (2), add 600 mL of toluene and 5 g of rutile nano-titanium dioxide into a reaction container equipped with a condenser reflux tube, disperse it by ultrasonication, then add 4 g of toluene-2,4-diisocyanate, heat to 110° C., react for 2 h, filter, wash with toluene, and dry to obtain modified rutile nano-titanium dioxide.

[0027] Example 2

[0028] Step (1), add 100 mL of water and 12 g of titanium tetrachloride to a reaction vessel under an ice bath, stir, add 600 mL of n-hexanol and 8 g of sodium dodecyl sulfate, stir and mix, pour the solution into a reaction kettle, heat to 100° C., react for 12 h, filter, wash with water and ethanol in turn, and dry to obtain rutile nano-titanium dioxide.

[0029] Step (2), add 600 mL of toluene and 5 g of rutile nano-titanium dioxide into a reaction container equipped with a condenser reflux tube, disperse it by ultrasonication, then add 2 g of toluene-2,4-diisocyanate, heat to 100° C., react for 3 h, filter, wash with toluene, and dry to obtain modified rutile nano-titanium dioxide.

[0030] Example 3

[0031] Step (1), add 100 mL of water and 15 g of titanium tetrachloride to a reaction vessel under an ice bath, stir, add 650 mL of n-hexanol and 10 g of sodium dodecyl sulfate, stir and mix, pour the solution into a reaction kettle, heat to 80° C., react for 18 h, filter, wash with water and ethanol in turn, and dry to obtain rutile nano-titanium dioxide.

[0032] Step (2), add 800 mL of toluene and 5 g of rutile nano-titanium dioxide into a reaction container equipped with a condenser reflux tube, disperse it by ultrasonication, then add 5 g of toluene-2,4-diisocyanate, heat to 110° C., react for 2 h, filter, wash with toluene, and dry to obtain modified rutile nano-titanium dioxide.

[0033] Comparative Example 1

[0034] Step (1), add 100 mL of water and 20 g of titanium tetrachloride to a reaction vessel under an ice bath, stir and then add 700 mL of n-hexanol, stir and mix, pour the solution into a reaction kettle, heat to 90° C., react for 18 hours, filter, wash with water and ethanol in turn, and dry to obtain rutile nano-titanium dioxide.

[0035] Step (2), add 600 mL of toluene and 5 g of rutile nano-titanium dioxide into a reaction container equipped with a condenser reflux tube, disperse it by ultrasonication, then add 4 g of toluene-2,4-diisocyanate, heat to 110° C., react for 2 h, filter, wash with toluene, and dry to obtain modified rutile nano-titanium dioxide.

[0036] The X-ray diffractometer was used to characterize the rutile nano-titanium dioxide. The average size D of the nano-titanium dioxide grains was tested by X-ray broadening method.

[0037] D = K × λ / (β × cosθ). K is a constant of 0.89; λ is the wavelength of X-rays; θ is the half diffraction angle; β is the half-height width of the strongest diffraction peak in the XRD spectrum. The test results are shown in Table 1.

[0038] Table 1 Average size of nano-titanium dioxide grains

[0039]

[0040] Example 4

[0041] (1) Add 300 mL of tetrahydrofuran, 20 g of bis(4-aminophenoxy)dimethylsilane, and 22 g of glycidyl methacrylate into a reaction container, heat to 40° C., stir to react for 5 h, distill under reduced pressure, wash with petroleum ether and acetone in turn, and dry to obtain acrylate dimethylsilane monomer.

[0042] (2) Add 800 mL of toluene, 100 g of styrene, and 10 g of acrylate dimethylsilane monomer into a reaction container, introduce nitrogen, add 0.5 g of azobisisobutyronitrile, heat to 85° C., react for 7 h, distill under reduced pressure, wash with ethanol, and dry to obtain a polystyrene copolymer.

[0043] (3) Add 1 kg of polystyrene copolymer, 5 g of modified rutile nano-titanium dioxide (prepared according to the method of Example 1), and 4 g of antioxidant 1010 into a twin-screw extruder, and the temperatures of sections 1-5 are 190°C, 200°C, 220°C, 220°C, and 215°C. Melt blending, extrusion, and granulation are performed to obtain high temperature resistant and aging resistant polystyrene.

[0044] Example 5

[0045] (1) Add 250 mL of tetrahydrofuran, 20 g of bis(4-aminophenoxy)dimethylsilane, and 20.6 g of glycidyl methacrylate to a reaction container, heat to 40° C., stir to react for 5 h, distill under reduced pressure, wash with petroleum ether and acetone in turn, and dry to obtain acrylate dimethylsilane monomer.

[0046] (2) Add 1000 mL of toluene, 100 g of styrene, and 20 g of acrylate dimethylsilane monomer into a reaction container, introduce nitrogen, add 0.56 g of azobisisobutyronitrile, heat to 75° C., react for 10 h, distill under reduced pressure, wash with ethanol, and dry to obtain a polystyrene copolymer.

[0047] (3) Add 1 kg of polystyrene copolymer, 5 g of modified rutile nano-titanium dioxide (prepared according to the method of Example 1), and 4 g of antioxidant 1010 into a twin-screw extruder, and the temperatures of sections 1-5 are 190°C, 200°C, 220°C, 220°C, and 215°C. Melt blending, extrusion, and granulation are performed to obtain high temperature resistant and aging resistant polystyrene.

[0048] Example 6

[0049] (1) Add 300 mL of tetrahydrofuran, 20 g of bis(4-aminophenoxy)dimethylsilane, and 20.6 g of glycidyl methacrylate to a reaction container, heat to 50° C., stir to react for 3 h, distill under reduced pressure, wash with petroleum ether and acetone in turn, and dry to obtain acrylate dimethylsilane monomer.

[0050] Step (2), add 1000 mL of toluene, 100 g of styrene, and 30 g of acrylate dimethylsilane monomer into a reaction container, introduce nitrogen, add 0.65 g of azobisisobutyronitrile, heat to 70° C., react for 10 h, distill under reduced pressure, wash with ethanol, and dry to obtain a polystyrene copolymer.

[0051] Step (3), add 1 kg of polystyrene copolymer, 5 g of modified rutile nano-titanium dioxide (prepared according to the method of Example 1), and 4 g of antioxidant 1010 into a twin-screw extruder, and the temperatures of sections 1-5 are 190°C, 200°C, 220°C, 220°C, and 215°C. Melt blending, extrusion, and granulation are performed to obtain high temperature resistant and aging resistant polystyrene.

[0052] Example 7

[0053] (1) Add 1 kg of polystyrene copolymer (prepared according to the method of Example 4), 20 g of modified rutile nano-titanium dioxide (prepared according to the method of Example 1), and 4 g of antioxidant 1010 into a twin-screw extruder, and melt blend, extrude, and granulate at sections 1-5 of 190°C, 200°C, 220°C, 220°C, and 215°C to obtain high temperature resistant and aging resistant polystyrene.

[0054] Example 8

[0055] (1) Add 1 kg of polystyrene copolymer (prepared according to the method of Example 4), 40 g of modified rutile nano-titanium dioxide (prepared according to the method of Example 1), and 4 g of antioxidant 1010 into a twin-screw extruder, and melt blend, extrude, and granulate at sections 1-5 of 190°C, 200°C, 220°C, 220°C, and 215°C to obtain high temperature resistant and aging resistant polystyrene.

[0056] Comparative Example 2

[0057] (1) Add 1 kg of polystyrene copolymer (prepared according to the method of Example 4) and 4 g of antioxidant 1010 into a twin-screw extruder, and melt blend, extrude and granulate at the temperatures of sections 1-5 of 190°C, 200°C, 220°C, 220°C and 215°C to obtain high temperature resistant and anti-aging polystyrene.

[0058] Comparative Example 3

[0059] (1) Add 1 kg of polystyrene copolymer (prepared according to the method of Example 4), 5 g of rutile nano-titanium dioxide (prepared according to the method of Example 1), and 4 g of antioxidant 1010 into a twin-screw extruder, and melt blend, extrude, and granulate at sections 1-5 of 190°C, 200°C, 220°C, 220°C, and 215°C to obtain high temperature resistant and aging resistant polystyrene.

[0060] Comparative Example 4

[0061] (1) Add 800 mL of toluene and 100 g of styrene into a reaction vessel, introduce nitrogen, add 0.5 g of azobisisobutyronitrile, heat to 85°C, react for 7 h, distill under reduced pressure, wash with ethanol, and dry to obtain polystyrene.

[0062] (2) Add 1 kg of polystyrene, 5 g of modified rutile nano-titanium dioxide (prepared according to the method of Example 1), and 4 g of antioxidant 1010 into a twin-screw extruder, and the temperatures of sections 1-5 are 190°C, 200°C, 220°C, 220°C, and 215°C. Melt blending, extrusion, and granulation are performed to obtain high temperature resistant and aging resistant polystyrene.

[0063] The polystyrene was compression molded in a flat vulcanizer at a pressure of 10 MPa, a temperature of 210°C, and a time of 15 min to form a sheet. The tensile properties were tested according to GB / T 1040.1-2018.

[0064] The polystyrene sheet was placed in a UV accelerated aging test chamber for 240 hours at a light intensity of 40 mW / cm 2 ; Relative humidity 60%. Then the tensile properties were tested. The test results are shown in Table 2.

[0065] Table 2 Polystyrene sheet tensile properties test

[0066]

[0067]

[0068] It can be seen from the above table that, compared with Comparative Example 2, the modified rutile nano-titanium dioxide is added to the high temperature resistant and aging resistant polystyrene in Examples 4-6, and the tensile strength and elongation at break are significantly improved, reaching 28.0-29.1 MPa and 54.2-54.8%.

[0069] And after ultraviolet aging, the tensile strength and elongation at break decrease very little. Taking Example 4 as an example, the retention rate of tensile strength before and after aging is 28.2÷29.1=96.91%, and the retention rate of elongation at break is 52.4÷54.2=96.68%. It has good anti-ultraviolet aging performance.

[0070] The retention rate of tensile strength before and after aging in comparative example 2 is 21.6÷24.1=89.63%, and the retention rate of elongation at break is 42.6÷48.6=87.65%. The retention rates of tensile strength and elongation at break are significantly lower than those in Example 4. This is mainly because modified rutile nano-titanium dioxide is added in Examples 4-6. After the rutile nano-titanium dioxide is modified with toluene diisocyanate, its dispersibility is better, and its compatibility with the polystyrene copolymer matrix is ​​excellent, which is beneficial to improving the tensile properties of polystyrene; at the same time, the isocyanate groups contained on the surface of the modified rutile nano-titanium dioxide can react with the hydroxyl group of the polystyrene copolymer during high-temperature melt blending in a screw extruder, thereby grafting the nano-titanium dioxide into the polystyrene copolymer molecular chain, enhancing the bonding strength between the two, so that the nano-titanium dioxide plays a better reinforcing role, and further improves the tensile strength and elongation at break of polystyrene. In addition, rutile nano-titanium dioxide has a strong ability to absorb ultraviolet rays and is evenly dispersed in the polystyrene matrix, significantly improving its anti-ultraviolet aging performance.

[0071] Compared with Example 4, Comparative Example 3 adds unmodified rutile nano-titanium dioxide, which has poor compatibility with the polystyrene matrix and does not contain isocyanate groups, and cannot react with the hydroxyl groups of the polystyrene copolymer. The bonding strength between the two is low, resulting in a low reinforcement effect of the nano-titanium dioxide, and the tensile strength and elongation at break of the polystyrene material are lower than those of Example 4.

[0072] The polystyrene in Comparative Example 4 does not contain hydroxyl groups and cannot react with the isocyanate groups of the modified rutile nano-titanium dioxide. The bonding strength between the two is low, resulting in poor reinforcement effect of the nano-titanium dioxide. The tensile strength and elongation at break of the polystyrene material are lower than those in Example 4.

[0073] Weigh 6 mg of high temperature resistant and anti-aging polystyrene, place it in a thermogravimetric analyzer, and perform thermal properties in a nitrogen atmosphere at a heating rate of 10°C / min and a test temperature of 30-800°C. The test results are shown in Table 3.

[0074] Table 3 Polystyrene thermal performance test

[0075]

[0076] As can be seen from the above table, compared with Comparative Example 4, the initial thermal decomposition temperature and the maximum thermal decomposition rate temperature of each embodiment, as well as Comparative Example 2 and Comparative Example 3 are significantly improved, mainly because the polystyrene copolymer molecular chain contains a diphenylsiloxane structure, has strong heat resistance, and has good thermal decomposition resistance, which is conducive to improving the heat resistance of the material. In addition, the isocyanate group of the modified rutile nano-titanium dioxide in each embodiment reacts with the hydroxyl group of the polystyrene copolymer to form a chemical crosslinking effect between the nano-titanium dioxide and the polystyrene, thereby increasing the crosslinking degree of the polystyrene molecular chain and restricting the movement of the molecular chain, thereby increasing the thermal decomposition temperature of the polystyrene material, showing a higher initial (5% mass loss) thermal decomposition temperature and maximum thermal decomposition rate temperature, and significantly improving the high temperature resistance of the material.

[0077] The above describes some embodiments of the present invention, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.

Claims

1. A method for preparing modified rutile nano-titanium dioxide, characterized in that: The preparation method comprises the following steps: Step (1), adding water and titanium tetrachloride to a reaction vessel under an ice bath, stirring, adding n-hexanol and sodium dodecyl sulfate, stirring and mixing, pouring the solution into a reaction kettle, filtering after the reaction, washing, and drying to obtain rutile nano-titanium dioxide; Step (2), adding toluene and rutile nano-titanium dioxide into a reaction container, dispersing by ultrasonication, then adding toluene-2,4-diisocyanate, heating to 100-110° C., reacting for 2-3 hours, filtering, washing, and drying to obtain modified rutile nano-titanium dioxide.

2. The method for preparing modified rutile nano-titanium dioxide according to claim 1, characterized in that: In the step (1), the ratio of water, titanium tetrachloride, n-hexanol and sodium dodecyl sulfate is 1L:(120-200)g:(6-7)L:(80-130)g.

3. The method for preparing modified rutile nano-titanium dioxide according to claim 1, characterized in that: The reaction temperature in step (1) is 80-100° C. and the reaction time is 12-18 hours.

4. The method for preparing modified rutile nano-titanium dioxide according to claim 1, characterized in that: In the step (2), the ratio of rutile nano-titanium dioxide to toluene-2,4-diisocyanate is 1 g:(0.4-1) g.

5. Use of modified rutile nano-titanium dioxide obtained by the preparation method according to any one of claims 1 to 4 in high temperature resistant and anti-aging polystyrene.

6. The use according to claim 5, characterized in that: The preparation method of the high temperature resistant and aging resistant polystyrene comprises the following steps: Step A, adding tetrahydrofuran, bis(4-aminophenoxy)dimethylsilane in a ratio of 1 g:(1.03-1.1) g, and glycidyl methacrylate into a reaction container, heating to 40-50° C., stirring for reaction for 3-5 hours, distilling under reduced pressure, washing, and drying to obtain acrylate dimethylsilane monomer; Step B, adding toluene, styrene, and acrylate dimethylsilane monomer into a reaction container, introducing nitrogen, adding azobisisobutyronitrile, distilling under reduced pressure after the reaction, washing, and drying to obtain a polystyrene copolymer; Step C: adding polystyrene copolymer, modified rutile nano-titanium dioxide and antioxidant into a twin-screw extruder, melt blending, extruding and granulating to obtain high temperature resistant and anti-aging polystyrene.

7. The use according to claim 6, characterized in that: In the step B, the mass ratio of styrene to acrylate dimethylsilane monomer is 1 g:(0.1-0.3) g.

8. The use according to claim 6, characterized in that: In the step C, the mass ratio of the polystyrene copolymer to the modified rutile nano-titanium dioxide is 100 g:(0.5-4) g.

9. The use according to claim 6, characterized in that: The reaction temperature in step C is 70-85° C. and the reaction time is 7-10 h.

10. The use according to claim 6, characterized in that: The temperature of sections 1-5 of the twin-screw extruder is 190-220°C.

Citation Information

Patent Citations

  • Antistatic and flame-retardant rutile titanium dioxide loaded tin antimony oxide / expanded polystyrene composite material as well as preparation method and application thereof

    CN118256042A

  • Synthetic method of nano-rutile

    CN104649316A

  • Composite auxiliary agent capable of improving aging resistance of polymer and preparation method thereof

    CN110157043A

  • Mixed crystal phase TiO2 grafted polymethyl methacrylate denture base resin and preparation method thereof

    CN113402721A

  • Stretch-resistant cellulose-TiO2 grafted polyvinyl alcohol antibacterial plastic film and preparation method thereof

    CN113773537A

Cited By

  • Composite material for electrode insulation support frame and preparation method thereof

    CN121758865A